NMR-based Fragment Screening of Inhibitors Against p300 CH1 and HIF-1 CTAD Interaction - Eo, Yumi; Shim, Myungbo; Thuy Nguyen Thi Phuong; Phuong Pham Hoa; Ahn, Dae-Ro; Ahn, Hee-Chul (WILEY-V C H VERLAG GMBH, 2016)
NMR spectroscopy of p300 CH1 and HIF-1 CTAD complex was conducted to investigate the conformational status of the complex and to screen the protein-protein interaction inhibitors. The individual p300 CH1 and HIF-1 CTAD were unstructured or partially structured; however, the complex had well-defined folded structure. Since the H-1-N-15 HSQC spectrum of p300 CH1 or HIF-1 CTAD in the free state was completely different from that in the bound state, it was possible to discriminate whether the protein was in the complex state or not. Fragment compounds were titrated to p300 CH1 and HIF-1 CTAD complex and some showed inhibition of protein-protein interaction based on the analyses of NMR spectra. The result shows that NMR-based screening is possible to discover the fragment chemicals which inhibit the formation of p300 CH1 and HIF-1 CTAD complex.
Keywords: HYPOXIA-INDUCIBLE FACTOR-1; PROLYL HYDROXYLATION; CBP/P300; PROTEIN; ALPHA; STABILIZATION; TRANSCRIPTION; RECRUITMENT; HOMEOSTASIS; BINDING